2020
DOI: 10.4103/jpbs.jpbs_60_20
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of suprabasal cell layer in oral epithelial dysplasia: A computer-assisted microscopic study

Abstract: A BSTRACT Background: Oral leukoplakia is the most common precancerous lesion. Various grading systems based on histological findings have been proposed for dysplasia. Recently, computer-assisted morphometric analysis has been established to reduce the interobserver and intraobserver variability during the histological grading of epithelial dysplasia. This study was undertaken to establish the morphometric changes in the suprabasal cell layer of different grades of oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…The authors acknowledge that support systems for OED grading should overcome this percentage but particularities in the data curation and the investigated disorders should be considered. A statistically significant increase in nuclear volume density, nuclear‐cell ratio, nuclear area, and perimeter are found in dysplastic cells when compared within different dysplasia grades, with higher values in increasing grades 28 . This premise corroborates that shape and size of nuclei can help in the differentiation among dysplasia grading.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The authors acknowledge that support systems for OED grading should overcome this percentage but particularities in the data curation and the investigated disorders should be considered. A statistically significant increase in nuclear volume density, nuclear‐cell ratio, nuclear area, and perimeter are found in dysplastic cells when compared within different dysplasia grades, with higher values in increasing grades 28 . This premise corroborates that shape and size of nuclei can help in the differentiation among dysplasia grading.…”
Section: Discussionsupporting
confidence: 66%
“…A statistically significant increase in nuclear volume density, nuclear-cell ratio, nuclear area, and perimeter are found in dysplastic cells when compared within different dysplasia grades, with higher values in increasing grades. 28 LR. However, annotations enrolling all the epithelium extension associated with the fragmentation process may insert bias by providing a great intersection of features that characterize both OED classes when using the BS grading system.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have tried to use image analysis to improve tissue diagnosis of cancer [1][2][3][4]. There has been a lot of research that showed the possible role of computer-aided cell morphometry in diagnosis of lesions and predicting clinical outcomes [5][6][7][8]. Most of these works studied nuclear morphometry in terms of nuclear size and area.…”
Section: Introductionmentioning
confidence: 99%